2001
DOI: 10.1136/gut.48.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Severe imbalance of cell proliferation and apoptosis in the left colon and in the rectosigmoid tract in subjects with a history of large adenomas

Abstract: Background-Alterations in epithelial proliferation and apoptosis in colonic mucosa are associated with an increased risk of colon cancer. It is unclear if these alterations represent a generalised "field defect". Aims-To analyse segmental patterns of cell proliferation and apoptosis in the colon of subjects with a high and no apparent risk of colon cancer. Methods-Pancolonoscopywas performed in 15 patients with resected adenomas (>1.5 cm) and in nine subjects without an apparent risk of colorectal cancer. Muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 56 publications
4
42
0
2
Order By: Relevance
“…Neoplasms can arise when decreased apoptosis leads to the accumulation of genetically aberrant cells (9)(10)(11)(12). Thus, apoptosis may serve a protective role in the colorectal mucosa by preventing the development of adenomas and colorectal cancer (13)(14)(15). Observation of low apoptosis in the normal rectal mucosa supports the concept of a field effect, namely, that characteristics of the mucosa provide a substrate for the development of adenomas.…”
Section: Introductionsupporting
confidence: 48%
“…Neoplasms can arise when decreased apoptosis leads to the accumulation of genetically aberrant cells (9)(10)(11)(12). Thus, apoptosis may serve a protective role in the colorectal mucosa by preventing the development of adenomas and colorectal cancer (13)(14)(15). Observation of low apoptosis in the normal rectal mucosa supports the concept of a field effect, namely, that characteristics of the mucosa provide a substrate for the development of adenomas.…”
Section: Introductionsupporting
confidence: 48%
“…Nonetheless, comparisons between cell culture concentrations and plasma levels are somewhat artificial, because of the inability to accurately mimic in vivo metabolism and tissue concentration of the agent in epithelial or tumour cells. Decreased basal levels of apoptosis and hyperproliferative mucosa have been observed in patients with adenomas, suggesting the existence of a 'field defect' in the colonic mucosa (Anti et al, 2001). Although we observed proportionally less apoptosis at lower concentrations of aspirin, there is evidence that low levels of apoptosis translate into significant tumour regression over time in cell kinetics studies (Pritchard and Watson, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…20 Some studies have suggested the existence of a proximal to distal proliferative gradient in the normal colon, 21 although others have reported the opposite result 22 or no segmental variation. 23 The apoptotic index is lower in the right colon, possibly due to lower expression of the pro-apoptotic Bcl-2 homologue Bak compared to the left colonic mucosa. 24 Fermentation reactions leading to short-chain fatty acid production are up to 8-fold higher in the proximal compared to distal colon.…”
Section: Embryologic Morphologic Physiologic and Biochemical Differmentioning
confidence: 99%